MANAJEMEN PENGELOLAAN MUTU SEKOLAH; UPAYA MEMBANGUN SEKOLAH TERDEPAN DALAM BERINOVASI - Abu Hasan Agus R; M Idris Yamin; Muhammad Iqbal (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
Schools are an indispensable part of modern human life, especially since many jobs are determined by diploma ownership, based on that, schools can not only provide education well, but are required to improve quality management in school management to produce graduates who can compete both in the world of work and competition to enter the university level. This research will answer the management strategy to the leadership model in improving the quality of schools to innovate. The research method used is using a qualitative approach, with the type of field research by involving researchers as a whole with data collection techniques through observation, interviews, and documentation analysis. The results of research at Madrasah Aliyah Walisongo Gending in the implementation of education quality management, illustrated several relevant aspects: Certainty of Education Management Guidelines; Comprehensive Planning Strategies; Management of Institutions and Educators; Supervision; Evaluation; and Continuous Improvement; The Role of the Principal. From this conclusion, it appears that the management of education quality at Madrasah Aliyah Walisongo Gending has worked well in many aspects. However, there are still some areas that require further attention and improvement to enhance the overall quality of education.